Edukasi Swamedikasi Penyakit Kulit dengan Metode Cara Belajar Insan Aktif (CBIA) di Cileungsi, Jawa Barat - Nurhasnah; Viviandhari, Daniek; Maifitrianti (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
The practice of self-medication is relatively high among Indonesian people. Inappropriate self-medication practices can have a negative impact. One of the diseases that is often treated with self-medication is a skin disease. Community service activities were carried out on February 19, 2023, at the Al Barokah Musholla, Cileungsi. The activity was attended by 27 participants consisting of mothers. The method used in this activity was Community Based Interactive Approach (CBIA). The activity begins with a presentation about the management of skin disease. Furthermore, participants were divided into several groups, and participants were asked to discuss the medicines that had been provided. Participants put the results of the discussion on a worksheet accompanied by a tutor. Participants filled out pre-test and post-test questionnaires to see changes after being given education. The results of statistical analysis showed that there was an increase in participants' knowledge after being given education with a p-value of 0.011. It can be concluded that self-medication counseling activities on skin diseases with the CBIA method can increase participants' knowledge